2004
DOI: 10.1227/01.neu.0000097200.18478.7b
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Disorders with Spontaneous Spinal Cerebrospinal Fluid Leaks and Intracranial Hypotension: A Prospective Study

Abstract: Findings suggesting connective tissue disorders are common among patients with spontaneous spinal CSF leaks, and manifestations may be subtle. A variety of disorders can be identified, probably reflecting genetic heterogeneity. Problems with wound healing may occur as a result of the systemic nature of the underlying connective tissue disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
151
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(162 citation statements)
references
References 23 publications
0
151
0
4
Order By: Relevance
“…Most reported studies described either single or limited number of patients, thus increasing the risk of publication bias. [6][7][8][9] A review of the medical records of 58 patients with spontaneous CSF leaks found nine patients (seven females and two males) who exhibited some clinical features of a connective tissue disorder. 16 The limitations of this study are that detailed descriptions of the patients and methods of evaluation are not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reported studies described either single or limited number of patients, thus increasing the risk of publication bias. [6][7][8][9] A review of the medical records of 58 patients with spontaneous CSF leaks found nine patients (seven females and two males) who exhibited some clinical features of a connective tissue disorder. 16 The limitations of this study are that detailed descriptions of the patients and methods of evaluation are not available.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Several case reports and small studies, published in the neurosurgical literature, suggested a link between HDCT and spontaneous CSF leaks, but the precise prevalence is not clear. [6][7][8][9] Here we report the clinical and molecular findings in a cohort of 50 patients with spontaneous CSF leaks. We propose that there is a broad clinical basis for considering spontaneous CSF leak as a clinical manifestation of HDCT, and that those patients with spontaneous CSF leaks should be screened for connective tissue and vascular abnormalities.…”
Section: Introductionmentioning
confidence: 95%
“…Cerebral spine fluid leak has rarely been reported to cause postural hypotension and headache in individuals with classic EDS. 9 …”
Section: Neurologic Featuresmentioning
confidence: 99%
“…1 Mechanical factors combine with an underlying structural dural disorder to cause the primary spontaneous spinal CSF leak. 2,3 The prototypical patient with spontaneous intracranial hypotension presents with orthostatic headaches, has pachymeningeal enhancement on cranial MR imaging, and is treated with an epidural blood patch, as reflected by the revised 2004 diagnostic criteria according to the International Classification of Headache Disorders (ICHD-2). 4 However, it has become well established that the spectrum of clinical as well as radiographic manifestations of spontaneous intracranial hypotension is unusually broad, 1,5 and this is not reflected by the ICHD-2 criteria.…”
mentioning
confidence: 99%